2012
DOI: 10.1017/jfm.2012.353
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between flow-induced vibration mechanisms of a square cylinder with varying angles of attack

Abstract: International audienceThis study examines the influence of angle of attack of a square section cylinder on the cylinder's flow-induced vibration, where the direction of the vibration is transverse to the oncoming flow. Our experiments, which traversed the velocity-angle of attack parameter space in considerable breadth and depth, show that a low-mass ratio body can undergo combinations of both vortex-induced vibration and galloping. When the body has an angle of attack that makes it symmetric to the flow, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
130
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(153 citation statements)
references
References 42 publications
22
130
1
Order By: Relevance
“…Structural stiffness of the oscillating system was controlled by stainless-steel extension springs attached to both sides of the support carriage and the base of the air-bearing system. More details of this hydroelastic system can be found in Nemes et al (2012) and Zhao et al (2014a,b).…”
Section: Experimental Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Structural stiffness of the oscillating system was controlled by stainless-steel extension springs attached to both sides of the support carriage and the base of the air-bearing system. More details of this hydroelastic system can be found in Nemes et al (2012) and Zhao et al (2014a,b).…”
Section: Experimental Methodologymentioning
confidence: 99%
“…VIV and galloping need not occur mutually exclusively; their occurrence depends on the flow and structural properties. In fact, the two FIV phenomena may occur in the same flow regimes, as shown in Corless & Parkinson (1988), Nemes et al (2012) and Zhao et al (2014b). Nemes et al (2012) and Zhao et al (2014b) have shown that large amplitude response regions can result from the interaction between VIV and galloping.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have emphasized the impact of breaking the system symmetry, for example by forcing the circular body to rotate about its axis (Bourguet & Lo Jacono 2014), by placing it close to a side wall (Zhao & Cheng 2011) or by considering a non-circular cross-section (Nemes et al 2012). Typical effects of such symmetry breaking are the emergence of asymmetric wake patterns, the appearance of a time-averaged cross-flow force and the change of frequency ratio between the in-line and cross-flow forces and body oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have greatly enhanced our understanding of flow past a single cylinder both numerically and experimentally (Luo et al 1994;Williamson 1996;Zdravkovich 1997;Williamson and Govardhan 2004;Alonso et al 2009;Yoon et al 2010;Bao et al 2011;Nemes et al 2012). As confirmed in these works, some parameters, such as material properties of the cylinder, cross-section shape, flow incidence angle, and Reynolds number, can lead to significant changes in flow field, as well as flow-induced forces and vibrations of the cylinder.…”
Section: Introductionmentioning
confidence: 85%